2015
DOI: 10.1039/c5cp04280a
|View full text |Cite
|
Sign up to set email alerts
|

Unwilling U–U bonding in U2@C80: cage-driven metal–metal bonds in di-uranium fullerenes

Abstract: Endohedral actinide fullerenes are rare and a little is known about their molecular properties. Here we characterize the U2@C80 system, which was recently detected experimentally by means of mass spectrometry (Akiyama et al., JACS, 2001, 123, 181). Theoretical calculations predict a stable endohedral system, (7)U2@C80, derived from the C80:7 IPR fullerene cage, with six unpaired electrons. Bonding analysis reveals a double ferromagnetic (one-electron-two-center) U-U bond at an rU-U distance of 3.9 Å. This bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
96
4
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(112 citation statements)
references
References 81 publications
10
96
4
2
Order By: Relevance
“…The electron occupancy for its Er−Er bond is only 0.98 e, which, together with the much smaller bond order than the corresponding values of Er 2 @C 82,86 , suggests the possible formation of a weak single‐electron Er−Er bond. This kind of weak Er−Er bond can be named as an “unwilling metal–metal bond” where the metal atoms are strongly bound to the cage, which has been theoretically introduced in the U 2 @C 2 n (2 n =60, 80, 84, 90) series by Straka et al …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron occupancy for its Er−Er bond is only 0.98 e, which, together with the much smaller bond order than the corresponding values of Er 2 @C 82,86 , suggests the possible formation of a weak single‐electron Er−Er bond. This kind of weak Er−Er bond can be named as an “unwilling metal–metal bond” where the metal atoms are strongly bound to the cage, which has been theoretically introduced in the U 2 @C 2 n (2 n =60, 80, 84, 90) series by Straka et al …”
Section: Resultsmentioning
confidence: 99%
“…The electron occupancy for its ErÀEr bond is only 0.98 e, which, together with the much smaller bond order than the corresponding values of Er 2 @C 82,86 ,s uggests the possible formation of aw eak single-electron ErÀEr bond. This kind of weakE r ÀEr bond can be nameda sa n" unwillingm etal-metal bond" where the metal atoms are strongly bound to the cage, which has been theoretically introduced in the U 2 @C 2n (2n = 60, 80, 84, 90) series by Straka et al [27] Figure 3s hows the corresponding metal bonding orbitals, in which two and one singly occupied orbitals are found for Er 2 @C 82,86 and Er 2 @C 84 ,r espectively.T he metal contributionsi n the molecular orbitals (MOs) indicate that the shared electron betweent he two metal centers of Er 2 @C 84 stems from Er1. Consistently,t he calculated spin densitiess how large distributions on the two Er atoms in each Er 2 @C 2n ,w hereas the spin density distribution is also recognized between the two Er atoms in Er 2 @C 84 (Figure 4a), indicating the existence of the unpaired electron.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that fullerenes can stabilize enclosed metallic clusters by strong charge‐transfer interactions and covalent‐type of bonding with the cage . Recent experiments also revealed that fullerenes, though apolar, strongly interact with external anions, as was predicted from the multicenter covalency model of anion–π bonding .…”
Section: Figurementioning
confidence: 92%
“…Remarkably, their calculations revealed that the valence state of U changes between 3+ and 4+ in different isomeric cages. They also successfully synthesized and characterized the long‐dreamed U 2 @I h (7)‐C 80 , which features a weak U–U metal bond . Very recently, the first mixed metal actinide‐based EMF Sc 2 CU@I h (7)‐C 80 and the novel uranium carbide UCU@I h (7)‐C 80 were continually prepared and successfully characterized .…”
Section: Introductionmentioning
confidence: 99%